Human Pluripotent Stem Cell-Derived Neural Cells as a Relevant Platform for Drug Screening in Alzheimer’s Disease. - García-León, Juan Antonio; Cáceres Palomo, Laura; Sánchez-Mejías, Elisabeth; Mejías-Ortega, Marina; Núñez-Díaz, Cristina; Fernández-Valenzuela, Juan José; Sánchez-Varo, Raquel María; Dávila-Cansino, José Carlos; Vitorica Ferrández, Javier; Gutiérrez-Pérez, Antonia (MDPI, 2020)
Extracellular amyloid-beta deposition and intraneuronal Tau-laden neurofibrillary tangles are prime features of Alzheimer’s disease (AD). The pathology of AD is very complex and still not fully understood, since different neural cell types are involved in the disease. Although neuronal function is clearly deteriorated in AD patients, recently, an increasing number of evidences have pointed towards glial cell dysfunction as one of the main causative phenomena implicated in AD pathogenesis. The complex disease pathology together with the lack of reliable disease models have precluded the development of effective therapies able to counteract disease progression. The discovery and implementation of human pluripotent stem cell technology represents an important opportunity in this field, as this system allows the generation of patient-derived cells to be used for disease modeling and therapeutic target identification and as a platform to be employed in drug discovery programs. In this review, we discuss the current studies using human pluripotent stem cells focused on AD, providing convincing evidences that this system is an excellent opportunity to advance in the comprehension of AD pathology, which will be translated to the development of the still missing effective therapies.
Keywords: Alzheimer, Enfermedad de; Células madre - Investigación; Oligodendroglia; Alzheimer’s disease; Microglia; Astrocytes; 3D cultures; Human induced pluripotent stem cells (hiPSCs); Disease modeling; Oligodendrocytes; Brain organoids